Hot Spot Detections and Volcanic Changes on Io during the Juno Epoch: Orbits PJ5 to PJ55 - Jason E. Perry; Ashley Gerard Davies; David A. Williams; David M. Nelson (The Planetary Science Journal)
We report volcanic changes on Io since the last Galileo (2002) and New Horizons (2007) flybys as observed by NASA’s Juno spacecraft, examining Io’s volcanism down to the local scale (<10 km pixel ^−1 ). From 3428 Jovian Infrared Auroral Mapper image frames obtained between 2017 March 21 (PJ5) and 2023 October 15 (PJ55), a catalog of 2305 hot spot detections with temperatures >200 K at 325 individual sites of volcanic activity has been generated. Where possible, hot spot color temperature, emitting area, and power output are calculated. Some prominent areas of volcanic activity first identified or better resolved in Juno data (Tonatiuh, Lei-Kung Fluctus, Volund, Guaraci Fluctus, Seth Patera, and others) are described. We examined their appearance, volcanological and geological settings, observed thermal emission, and evolving behavior, and quantified the changes that have taken place. Volcanic activity at Tonatiuh and Guaraci Fluctus, the sites of newly imaged lava flows, are examined in detail. At Tonatiuh, JunoCam data provide important context; at Guaraci Fluctus, the combination of data from multiple assets yields a comprehensive understanding of the evolution of a specific eruption episode. We further examine different types of active paterae, some possibly containing lava lakes. A group of bright eruptions are identified whose spatial and temporal locations suggest regional clustering. Our estimates of volcanic thermal emission are broadly consistent with previous analyses of spacecraft data. All derived products are available from the Io Geographical Information System database at Arizona State University. Appendix A contains newly approved feature names.